ChemInform Abstract: Synthesis of α‐Dawson‐Type Silicotungstate [α‐Si2W18O62]8‐ and Protonation and Deprotonation Inside the Aperture Through Intramolecular Hydrogen Bonds. Issue 31 (5th August 2014) - Minato, Takuo; Suzuki, Kosuke; Kamata, Keigo; Mizuno, Noritaka
Abstract α‐Dawson‐type silicotungstates (III), (IV), and (V) are synthesized by dimerization of a trivacant lacunary α‐Keggin‐type silicotungstate (II) under mild conditions.